Trophic State of the AKAP Reservoir, Payung Sekaki District, Pekanbaru Based on the Trophic State Index (TSI) - Olivia, Reyka Kristin; H Simarmata, Asmika; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Trophic State Index (TSI) is a method used to determine the trophical state of waters. The TSI was calculated based on physical, chemical and biological parameters and it is more representative for analysing the trophical state of waters. This research was conducted in March to April 2018 and it aims to understand the trophic state of the Akap Resevoir. There were three sampling stations namely Station 1 (inlet), Station 2 (in the middle of Akap Reservoir), and Station 3 (outlet). Samplings were done once/week for 3 weeks period. Water quality parameter measured were chlorophyll-a, total phosphorus, transparency, temperature, pH, nitrate, and free carbondioxide. Trophic status was calculated based on Carlson’s TSI. Results shown that the transparency was 24-30 cm, total phosphorus 0.24-0.54 mg/L, chlorophyll-a 25.56-38.38 µg/L, depth 1.63-2.53 m, temperature29-30 0C, pH 5-5.6, dissolved oxygen 2.95-3.28 mg/L and free carbondioxide 7.99-11.98 mg/L, TSI value 67.55-69.9. Based on Carlson’s TSI value, the  Akap Reservoir  can be categorized as moderate eutrophic. Keywords :Akap dam,Chlorophyll-a, Moderate eutrophic